IGF-binding proteins 3 and 4 are regulators of sprouting angiogenesis - Marchien G. Dallinga; Yasmin I. Habani; Richelle P. Kayser; Cornelis J. F. Van Noorden; Ingeborg Klaassen; Reinier O. Schlingemann (Molecular Biology Reports, 2020)
Purpose We have previously identified insulin-like growth factor 2 (IGF2) and insulin-like growth factor 1 receptor (IGF1R) as essential proteins for tip cell maintenance and sprouting angiogenesis. In this study, we aim to identify other IGF family members involved in endothelial sprouting angiogenesis. Methods Effects on sprouting were analyzed in human umbilical vein endothelial cells (HUVECs) using the spheroid-based sprouting model, and were quantified as mean number of sprouts per spheroid and average sprout length. RNA silencing technology was used to knockdown gene expression. Recombinant forms of the ligands (IGF1 and IGF2, insulin) and the IGF-binding proteins (IGFBP) 3 and 4 were used to induce excess effects. Effects on the tip cell phenotype were analyzed by measuring the fraction of CD34 + tip cells using flow cytometry and immunohistochemistry in a 3D angiogenesis model. Experiments were performed in the presence and absence of serum. Results Knockdown of IGF2 inhibited sprouting in HUVECs, in particular when cultured in the absence of serum, suggesting that components in serum influence the signaling of IGF2 in angiogenesis in vitro. We then determined the effects of IGFBP3 and IGFBP4, which are both present in serum, on IGF2-IGF1R signaling in sprouting angiogenesis in the absence of serum: knockdown of IGFBP3 significantly reduced sprouting angiogenesis, whereas knockdown of IGFBP4 resulted in increased sprouting angiogenesis in both flow cytometry analysis and immunohistochemical analysis of the 3D angiogenesis model. Other IGF family members except INSR did not affect IGF2-IGF1R signaling. Conclusions Serum components and IGF binding proteins regulate IGF2 effects on sprouting angiogenesis. Whereas IGFBP3 acts as co-factor for IGF2-IGF1R binding, IGFBP4 inhibits IGF2 signaling.

IGF2 and IGF1R identified as novel tip cell genes in primary microvascular endothelial cell monolayers - Marchien G. Dallinga; Bahar Yetkin-Arik; Richelle P. Kayser; Ilse M. C. Vogels; Patrycja Nowak-Sliwinska; Arjan W. Griffioen; Cornelis J. F. van Noorden; Ingeborg Klaassen; Reinier O. Schlingemann (Angiogenesis, 2018)

Rapid optimization of drug combinations for the optimal angiostatic treatment of cancer - Andrea Weiss; Xianting Ding; Judy R. van Beijnum; Ieong Wong; Tse J. Wong; Robert H. Berndsen; Olivier Dormond; Marchien Dallinga; Li Shen; Reinier O. Schlingemann; Roberto Pili; Chih-Ming Ho; et al. (Angiogenesis, 2015)
Drug combinations can improve angiostatic cancer treatment efficacy and enable the reduction of side effects and drug resistance. Combining drugs is non-trivial due to the high number of possibilities. We applied a feedback system control (FSC) technique with a population-based stochastic search algorithm to navigate through the large parametric space of nine angiostatic drugs at four concentrations to identify optimal low-dose drug combinations. This implied an iterative approach of in vitro testing of endothelial cell viability and algorithm-based analysis. The optimal synergistic drug combination, containing erlotinib, BEZ-235 and RAPTA-C, was reached in a small number of iterations. Final drug combinations showed enhanced endothelial cell specificity and synergistically inhibited proliferation ( p p p p